The Influence of Position of Durian in Determination of Ripeness of Durian Non-Destrucyively by Ultrasonic Wave - Bambang Haryanto; I Wayan Budiastra; Amoranto Trisnobudi (PERTETA, 2000)
The study was conducted to assess the influence of durian 's position toward transmission properties of ultrasonic wave for determination of the fruit ripeness using non-destructiive technique. Three ripe and unripe durian were used to assess transmittance wave that was passed the durian. The measurement was conducted at 3 peak and valley positions and it was repeated 20 times. The result showed that position durian 's inJluenccad thetransmissions of ultrasonic wave. Mo mzJ a (attenuation) values can be used as indicator for durian ripeness. Ripe durian tends to have highera value than unripe durian.